The House/Palace in Annunciations of the 15th Century: An Iconographic Interpretation in the Light of the Latin Patristic and Theological Tradition - Salvador-González, José María (Eikón / Imago, 2021)
This article seeks to highlight the doctrinal meanings enclosed in the representation of the house of Mary in the form of a palace or an aristocratic residence in seven images of the Annunciation of the 15th century. To justify our iconographic interpretations in this sense, we based on the analysis of many exegetical comments with which many Latin Fathers and theologians interpreted several metaphorical expressions with dogmatic projection, such as domus Sapientiae, domus Dei, aula regia, palatium Regis, domicilium Trinitatis, and other analogous terms. As a methodological strategy, we use here a double comparative analysis: in the first instance, analyzing a series of patristic and theological texts that exegetically interpret the metaphors above; secondly, relating these exegetical texts with the eight Annunciations explained here.